1998
DOI: 10.1097/00008483-199811000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Cardiac Rehabilitation Improves the Control of Dyslipidemia in Secondary Prevention

Abstract: Patients with CHD included in a comprehensive cardiac rehabilitation program showed a significantly better response to the hypolipidemic treatment than patients without cardiac rehabilitation. These results could be attributable to the extensive educational program on secondary prevention performed during cardiac rehabilitation, leading to optimized knowledge on lipid-lowering diet and to improved diet and drug adherence. A secondary prevention educational program must be an important part of any comprehensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
2
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 24 publications
0
15
2
1
Order By: Relevance
“…Furthermore, Verges B. et al showed in their research that CVR can improve response to the hypolipidemic therapy in patients with CHD. However, the average duration of CVR in this study was two months (42). On the other hand, we noted an improvement in red blood count which can have a positive impact on functional capacity (43).…”
Section: Discussioncontrasting
confidence: 54%
“…Furthermore, Verges B. et al showed in their research that CVR can improve response to the hypolipidemic therapy in patients with CHD. However, the average duration of CVR in this study was two months (42). On the other hand, we noted an improvement in red blood count which can have a positive impact on functional capacity (43).…”
Section: Discussioncontrasting
confidence: 54%
“…Their study effect should be more related to the progressive titration of lipid‐lowering drug therapy in addition to active lifestyle modification. The other three studies (Verges et al. 1998, Vale et al.…”
Section: Discussionmentioning
confidence: 99%
“…Verges et al (1998) compared the outcome of hypolipidemic treatment (referral to a dietician and a lipidologist) as part of cardiac rehabilitation with a control group of patients only seen by a dietician and a lipidologist. In the study group a signi®cantly greater reduction of total cholesterol (23 versus 13%), LDL cholesterol (28 versus 12%), the LDL/HDL ratio (34 versus 13%) and triglycerides (33 versus 21%) was seen, whereas there was no dierence in the use of hypolipidemic treatment (Verges et al 1998).…”
Section: Effect On Dyslipidaemia and Being Overweightmentioning
confidence: 99%
“…Verges et al (1998) compared the outcome of hypolipidemic treatment (referral to a dietician and a lipidologist) as part of cardiac rehabilitation with a control group of patients only seen by a dietician and a lipidologist. In the study group a signi®cantly greater reduction of total cholesterol (23 versus 13%), LDL cholesterol (28 versus 12%), the LDL/HDL ratio (34 versus 13%) and triglycerides (33 versus 21%) was seen, whereas there was no dierence in the use of hypolipidemic treatment (Verges et al 1998). Similar ®ndings were reported by Ades et al (1999), who showed that the systematic lipid review and physical training in a comprehensive rehabilitation programme resulted in a threefold increase of pharmacological modi®cations and lower LDL cholesterol values among the participants compared to patients receiving standard care.…”
Section: Effect On Dyslipidaemia and Being Overweightmentioning
confidence: 99%